Nitric oxide synthase 2 is involved in the pro-tumorigenic potential of γδ17 T cells in melanoma. (2nd August 2016) - Douguet, Laetitia; Bod, Lloyd; Lengagne, Renée; Labarthe, Laura; Kato, Masashi; Avril, Marie-Françoise; Prévost-Blondel, Armelle
ABSTRACT: γδ T lymphocytes may exert either protective or tumor-promoting functions in cancer, mostly based on their polarization toward interferon (IFN)-γ or interleukin (IL)-17 productions, respectively. Here, we demonstrate that γδ T cells accelerate the spontaneous metastatic melanoma development in a model of transgenic mice for the human RET oncogene (Ret mice). We identify unanticipated roles of inducible nitric oxide synthase (NOS2) in favoring the recruitment of pro-tumor γδ T cells within the primary tumor. γδ T cells isolated from Ret mice deficient for NOS2 produced more IFNγ and less IL-17 than their counterparts from Ret mice. By supporting IL-17 production by γδ T cells, NOS2 leads to the recruitment of polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) and metastasis formation. NOS2 also reduces the cytotoxicity of γδ T cells toward melanoma cells. Finally, we detected NOS2 expressing γδ T cells in the primary tumor and tumor-draining lymph nodes in Ret mice, but also in human melanoma. Overall our results support that this NOS2 autocrine expression is responsible for the polarization of γδ T cells toward a pro-tumor profile.